Evaluation of Dietary Inclusion of Specialty Protein Ingredients on Nursery Pig Performance - H. R. Williams; J. M. DeRouchey; M. D. Tokach; J. C. Woodworth; R. D. Goodband; S. S. Dritz; J. W. Frank; T. Wang (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 1,215 pigs (PIC 337 × 1050; initially 11.0 lb body weight) were used in a 42-d growth trial to evaluate a new specialty protein blend prototype (Protein Blend, International Ingredient Corp., St. Louis, MO) on nursery growth performance. Pigs were randomly assigned to pens (27 pigs per pen) and pens were allotted by weight to 1 of 5 dietary treatments in a randomized complete block design with 9 pens per treatment. Treatments were arranged in a 2 × 2 + 1 negative control factorial arrangement with main effects of protein source (HP300, Hamlet Protein, Findlay, OH; and Protein Blend) and 2 dietary levels (5 and 10%). Treatment diets were fed in two phases for 21 days (phase 1 = d 0 to 7; phase 2 = d 7 to 21). All pigs were then fed a common phase 3 diet from d 21 to 42. For the treatment period (d 0 to 21), there was a protein source effect with pigs fed diets containing HP300 having greater (P<0.05) average daily gain (ADG) and average daily feed intake (ADFI) and improved (P<0.05) feed efficiency (F/G) compared to pigs fed diets containing the Protein Blend. Also, ADG and ADFI decreased (linear,P<0.05) for pigs fed increasing levels of Protein Blend. Furthermore, pigs fed increasing levels of the Protein Blend had worse (quadratic,P= 0.050) F/G. Overall (d 0 to 42), there was a protein source effect in which pigs fed HP300 had improved (P<0.05) ADG and tendency (P<0.086) for improved F/G compared to pigs fed diets with the Protein Blend. Subsequent lab analysis revealed that Protein Blend was lower in crude protein and amino acids than formulated values. In summary, feeding the Protein Blend at increasing levels decreased performance compared to feeding diets containing HP300.
Keywords: growth; nursery pig; protein source